Bioengineered Nanoparticles: Bacterial Surfactant-assisted Synthesis of Silver Nanoparticles and their Multifunctional Applications - S, Jameer Ahamed.; S, Ancy Rosaly.; Balasubramanian, A.; C, S. Anu.; T, Citarasu. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Biosurfactants are surface-active agents synthesized by microorganisms, containing hydrophilic and hydrophobic domains. They lower surface tension at air/water interfaces and are primarily composed of polymeric heterosaccharide proteins. Nanotechnology manipulates nanoparticles, which have unique properties and biochemical and catalytic activity. Silver nanoparticles (AgNP) are popular due to their antibacterial and anti-inflammatory properties, used in various fields. In the current investigation, biosurfactant was extracted from the bacterial strains isolated from marine water samples at Chinna Muttom fishing harbor using a pure culture technique. These strains of were screened for surface activity assays for scrutinizing the strains. The biosurfactant was extracted using liquid-liquid extraction technique and yield was measured. The strains SF1 (CMST AJ 36) and SF2 (CMST AJ 53) had the highest yields, measuring 1.49 g/100 mL, 1.3 g/100 mL, and 1.28 g/100 mL from CMST AJ 56 respectively. Preliminary identification has done by TLC and ninhydrin test revealed the existence of a lipopetide and rhamnolipid band with Rf values of 0.90 (SF1) and 0.88 (SF2). However, the anthrone test indicated that SF3 contained glycolipids, with an Rf value of 0.74. The biosurfactant derivatives were further confirmed by GCMS, the mass spectrum data showed that all three biosufactants included hexadecanoic acid, niacin, cyclopentane hexyl-, and octadecanoic acid. This was corroborated by the detection of functional groups using FTIR, which showed the existence of lipopeptide moieties in SF1, SF2, and SF3 at 1402.15 cm−1 (N-H stretching) and 1454.23 cm−1 (C-O stretching), respectively. In contrast, the presence of carboxylic acid in all three SFs (1, 2, and 3) indicated the derivative of glycolipids, as shown by the peaks between 1403.12 and 1402.15 cm−1 with C=O stretch. Silver nanoparticles have been synthesized using extracted bacterial biosurfactants, namely SF AgNP1 (1.67 g/100 mL), SF AgNP2 (1.71 g/100 mL), and SF AgNP3 (1.62 g/100 mL), were estimated the corresponding yields. The reduction of the silver mental ion into the equivalent nanoparticles is indicated by the presence of peaks in the FTIR spectrum at 3417 (O-H Stretching), 2922 (C-H Strech), 1632 (C=O Group), and 1383 (C-N stretching). Moreover, the crystallographic data of 2θ peaks at 27.549, 31.954, and 45.969 further demonstrated the synthesized biosurfactant AgNps was crystalline or amorphous. Additionally, the size of the synthesized nanoparticles was characterized using SEM at 16.19 KV magnification, the size range of the produced biosurfactant AgNP (SF AgNP1) was 254.0 to 309.8 nm, whereas SF AgNP2 and SF AgNP3 showed 214.9 to 379.1 nm and 233.9 to 399.4 nm in diameter, respectively.